Impact of a Breach of The Rule of Law on Litigation in The Business Sector - Bogna BACZYNSKA (Communications of International Proceedings, 2021)
Since the Law and Justice party came to power in 2015, unfavourable changes have begun to take place in the Polish system of government and, more specifically, within the judiciary. The appointment of judges who do not meet constitutional requirements and the submission of courts and the Constitutional Tribunal to political pressure and political control has had far-reaching repercussions. The consequences are not only the lengthening of court proceedings, but also the increasing legal chaos and loss of confidence of citizens, including businesspeople, in the courts. Despite clear positions presented by various international organisations and European governments, as well as the European Union, Poland is still following the path of authoritarianism and violating the rule of law. One of the most important human rights - freedom of economic activity - is not duly protected. This is due to further restrictions introduced by the government against the judiciary. The courts, being the last bastion defending entrepreneurs, often no longer deserve the attribute of being independent and impartial bodies. The consequences are an unstable and uncomfortable situation for entrepreneurs, drops in international rankings, as well as a drastic reduction in the number of investments and the entrepreneurs' outflow to other countries.
Keywords: Freedom of Economic Activity; Entrepreneurs; Rule of Law; Courts.